IL-7/IL-7R在非小细胞肺癌中的表达及与淋巴转移和预后的关系 (Zhongguo Fei Ai Za Zhi, 2010)
BACKGROUND AND OBJECTIVE: It has been proven that lymph node metastasis was closely related to prognosis of lung cancer. Interleukin-7 (IL-7) and interleukin-7 receptor (IL-7R) could promote lymph node metastasis through vascular endothelial growth factor-D (VEGF-D). The aim of this study is to explore the expressions of IL-7 and IL-7R in lung cancer and the relationship between them with lymph node metastasis and prognosis in non-small cell lung cancer (NSCLC). METHODS: The expressions of IL-7 and IL-7R in 95 cases of NSCLC were detected with immunohistochemistry method and the relationship between IL-7 and IL-7R and their impact on lung cancer patients' outcomes were analyzed. RESULTS: In 95 cases of NSCLC, the high expression rates of IL-7, IL-7R and VEGF-D were 63.16%, 61.05% and 58.95%. The expressions of IL-7 and IL-7R were correlated closely with clinic stage and lymph node metastasis, but had no relationship with age, gender, histological type and differentiation degree. The lymphatic vessel density (LVD) mean of the group with high expressions of IL-7 and IL-7R was higher than that with low or negative expressions of IL-7 and IL-7R, and they were significant different in statistics. Log-rank analysis showed that the postoperative survival period was significantly shorter in high expression groups IL-7, IL-7R and VEGF-D comparing with that in low or negative groups. CONCLUSION: The high expression of IL-7 and IL-7R is highly positie correlated with clinic stage, lymph node metastasis, VEGF-D, LVD and poor prognosis in Non-small cell lung cancer.